Growth and condition indices of juvenile turbot, Scophthalmus maximus, exposed to contaminated sediments: Effects of metallic and organic compounds - Kerambrun, E.; Henry, Françoise; Perrichon, P.; Courcot, Lucie; Méziane, T.; Spilmont, Nicolas; Amara, Rachid (HAL CCSD, 2012)
International audience Since sediments have the potential to form associations with several classes of pollutants, they have been recognized as a possible and significant source of contamination for the benthic environment. Flatfish maintain a close association with sediments for food and cover, and are therefore more likely to be exposed to contaminated sediments, especially in coastal areas (e.g. nursery grounds). The assessment of these potential biological effects involves the use of adapted biomonitoring tools. The main objective of this study was to assess and compare the response of several physiological biomarkers measured on juvenile turbot (Scophthalmus maximus) exposed to contaminated sediments. Sediments were collected from three stations in a harbour in northern France (Boulogne-sur-Mer), in an anthropogenic French estuary (the Seine), and in a reference site (exposed sandy beach of Wimereux). Unexposed lab-reared juvenile turbots were exposed to sediments for 7 and 21 days in laboratory conditions. Sediments were analysed for metals, PAH and PCB contamination. Several fish growth and condition indices were individually analysed in fish according to the chemical contaminant availability in sediment, the metal concentrations in gills and the estimation of PAH metabolites in their bile. Significant decreases in growth rates, morphometric index, RNA:DNA ratio and the lipid storage index, based on the ratio of the quantity of triacylglycerols on sterols (TAG:ST), were observed with increasing level of chemical contamination. This decrease in the fish's physiological status could be related to the significant increase of several metal concentrations in contaminated fish gills and the significant increase of PAH metabolites in bile. In a field situation, such a reduction in growth and energetic status of juvenile fish could dramatically decrease their over-winter survival in contaminated nursery grounds.